Modulation of Cell Identity by Modification of Nuclear Pore Complexes - Gomar-Alba, Mercè; Mendoza, Manuel (Frontiers in Genetics, 2020)
Nuclear pore complexes (NPCs) are protein assemblies that form channels across the nuclear envelope to mediate communication between the nucleus and the cytoplasm. Additionally, NPCs interact with chromatin and influence the position and expression of multiple genes. Interestingly, the composition of NPCs can vary in different cell-types, tissues, and developmental states. Here, we review recent findings suggesting that modifications of NPC composition, including post-translational modifications, play an instructive role in cell fate establishment. In particular, we focus on the role of cell-specific NPC deacetylation in asymmetrically dividing budding yeast, which modulates transport-dependent and transport-independent NPC functions to determine the time of commitment to a new division cycle in daughter cells. By modulating protein localization and gene expression, NPC modifications are therefore emerging as central regulators of cell identity.